2023
DOI: 10.5398/tasj.2023.46.1.43
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Feed Quality of Fermented Tithonia diversifolia with Lactobacillus bulgaricus and Persea americana miller Leaves as Forages for Goat

Abstract: Fermented Tithonia diversifolia and Persea americana miller or avocado leaves as local alternative forages for goats are potential as protein, mineral, and energy sources. Therefore, this study aimed to evaluate the effect of fermented Tithonia diversifolia (FTD) and avocado leaves (AL) combination on in vitro nutrient digestibility, rumen fluid characteristics, and methane production. This study consisted of 3 trials. Trial 1 evaluated FTD's nutrient content with Lactobacillus bulgaricus with different durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The decrease in CH 4 gas production is directly proportional to the decrease in the protozoan population because the availability of H 2 for methanogens decreases, and a decrease in the protozoa population in the rumen results in a higher population of bacteria [ 49 ]. In addition, protein turnover in the rumen is lower and the amount of microbial protein that enters the duodenum increases [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in CH 4 gas production is directly proportional to the decrease in the protozoan population because the availability of H 2 for methanogens decreases, and a decrease in the protozoa population in the rumen results in a higher population of bacteria [ 49 ]. In addition, protein turnover in the rumen is lower and the amount of microbial protein that enters the duodenum increases [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus bulgaricus utilized the fermentable carbohydrate such as NFE (nitrogen free extract) that was available in fermented M. diversifolia. Pazla et al (2023) reported that the fermentation of T. diversifolia would reduce the content of NFE because NFE is a fermentable energy source for microbial growth. Serial dilution and method or culture technique can also affect the results of the calculation of the number of bacterial colonies.…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation of sugarcane tops using Pleurotus ostreatus and Aspergillus oryzae resulted in a pH of 6.83-6.98 (Pazla et al 2021b). Fermentation of Tithonia diversifolia using Lactobacillus bulgaricus produced a pH of 7.19-7.31 (Pazla et al 2023b).…”
Section: Ph Of Rumen Fluidmentioning
confidence: 99%